Pet avoidance in allergy cases: Is it possible to implement it? (2015)
ABSTRACT:Introduction: Among allergic patients, pet avoidance is commonly recommended. It is difficult for patients to accomplish this because of their emotional attachment to the pets, and its effectiveness is controversial. Objective: To explore the applicability and effectiveness of pet avoidance measures among sensitized patients. Materials and methods: We evaluated 288 patients with asthma, rhinitis, conjunctivitis and/or dermatitis using skin prick test to measure their sensitization to cats, dogs and other animals to which they were exposed. Exposure to animals was evaluated in each patient (pets at home, frequent indirect exposure or no exposure). In those patients sensitized to animals some avoidance measures, such as removing pets from home and preventing indirect exposure, were recommended. On the following two appointments, we evaluated patients’ fulfillment of these recommendations. Results: Sensitization to cats, dogs and birds was high (9%, 48%, 14%, respectively), as well as direct and indirect exposure (30%, 46%, 24%, respectively). Most patients denied contact with other animals (horses, hamsters, rabbits or cows), and sensitization to them was low. During the follow-up of patients sensitized to their pets at home (n=50), most of them refused to remove them from their house due to emotional attachment, and only two followed this recommendation. Conclusions: High exposure to animals could explain the frequency of sensitization to pets in this population. However, emotional attachment and prevalent indirect exposure to animals among sensitized patients make avoidance recommendations impractical or impossible to achieve.